Programmable Manipulations of Terahertz Beams by Graphene-Based Metasurface With Both Amplitude and Phase Modulations - Liu, Chenxi; Yang, Fei; Fu, Xiaojian; Wu, Junwei; Zhang, Lei (Frontiers in Materials, 2022)
Terahertz metasurface with digital, programmable control recently gained considerable attention for its potential applications in high-speed imaging, nondestructive sensing, and wireless communication. With elaborate design, the metasurface can perform amplitude, phase, and polarization modulations of electromagnetic waves. Most digital programmable metasurfaces focus on only one of the three dimensions. Here, we propose a graphene-based THz metasurface with both phase and amplitude modulations, which consists of an artificially constructed metal-insulator-metal structure and two-dimensional graphene material. Each meta-atom of the metasurface is divided into two sub-atoms, and the two sub-atoms can reflect terahertz waves with a phase difference of 180°. Meanwhile, the amplitude of the sub-atom can be effectively modulated or even switched off by applying different gate voltages to the graphene. By independently controlling the amplitude response of the two sub-atoms, the whole meta-atom can dynamically control both amplitude and phase responses of the cross-polarization waves. By carefully designing the coding patterns, the digital metasurface can control both beam direction and intensity, which may lead to various advanced applications in beam shaping, radar detection systems, and high-quality holography.